2017
DOI: 10.3892/etm.2017.4628
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect and mechanism of estrogen receptor β on myocardial infarction in mice

Abstract: The protective effect and the mechanism of estrogen receptor β (ERβ) on myocardial infarction (MI) in mice were explored. A total of 12 female Tg-ERβ transgenic mice and 12 non-transgenic littermate control (NLC) wild-type C57 mice were used for the present study. Both transgenic and wild-type mice had similar baseline data such as age, sex, and weight. The mouse model of MI was established by coronary artery ligation method, and the cardiac structure and function changes of the mouse were observed by ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, ERβ mediates cardioprotection in I/R on OVX mice through the PI3K/Akt pathway and anti-apoptotic signaling (decreased caspase-3 and -8 activities and increased Bcl-2) [ 64 ] and diminishes post-MI fibrosis [ 26 , 61 ]. ERβ could also influence arrhythmogenesis after MI, as infarcted females with ERβ deficiency show prolongation of ventricular repolarization and reduction in automaticity [ 65 ].…”
Section: Er Modulation and Mi: Preclinical Studiesmentioning
confidence: 99%
“…In addition, ERβ mediates cardioprotection in I/R on OVX mice through the PI3K/Akt pathway and anti-apoptotic signaling (decreased caspase-3 and -8 activities and increased Bcl-2) [ 64 ] and diminishes post-MI fibrosis [ 26 , 61 ]. ERβ could also influence arrhythmogenesis after MI, as infarcted females with ERβ deficiency show prolongation of ventricular repolarization and reduction in automaticity [ 65 ].…”
Section: Er Modulation and Mi: Preclinical Studiesmentioning
confidence: 99%
“…A recent study shows that rat cardiac fibroblast ER-α activation by E2 leads to inhibition of collagen I and III production in females, while E2 binding to ER-β promotes collagen production in males (51). However, another study shows that increased levels of ER-β after MI protect from inflammation and fibrosis formation in female mice (52). These studies do not have to be conflictive seeing that ER-α and -β dimerization inhibits collagen deposition, and an increased ER-β concentration could amplify this (51).…”
Section: (Perivascular) Fibrosis Formationmentioning
confidence: 99%
“…In recent years, in vivo and in vitro experiments have proven that the compound has positive anticancer, anti-inflammatory, antioxidative, neuroprotective, myocardial-protective, liver-protective, and kidney-protective effects ( 73 , 74 ). In addition, it has been reported that salidroside can inhibit the release of lactate dehydrogenase (LDH), creatine-kinase (CK) and aspartate aminotransferase (AST) from human cardiomyocytes by increasing the expression of HIF-1α, increasing the content of superoxide dismutase (SOD), increasing the activity of human cardiomyocytes, and reducing the death and apoptosis of cells ( 75 ). Overall, it was speculated that the main composition of RW may play a significant role in the treatment of AP through hub targets in these top-ranking signaling pathways.…”
Section: Discussionmentioning
confidence: 99%